A longitudinal study of C1q and anti-C1q autoantibodies in homologous and heterologous pregnancies for predicting pre-eclampsia - Agostinis, Chiara; Zito, Gabriella; Toffoli, Miriam; Peterlunger, Isabel; Simoni, Livia; Balduit, Andrea; Curtolo, Erica; Mangogna, Alessandro; Belmonte, Beatrice; Vacca, Davide; Romano, Federico; Stampalija, Tamara; et al. (Frontiers in Immunology, 2022)
C1q, the recognition molecule of the classical pathway of the complement system, plays a central role in pregnancy. Lack of C1q is characterized by poor trophoblast invasion and pregnancy failure. This molecule can be the target of an antibody response: anti‐C1q autoantibodies (anti-C1q) are present in several infectious and autoimmune diseases. The presence of these autoantibodies has been detected also in 2-8% of the general population. Recent evidence indicates that women who undergo assisted reproductive technology (ART) have an increased risk of developing pre-eclampsia (PE), particularly oocyte donation (OD) pregnancies. The aim of this study was to characterize the levels of C1q and anti-C1q in PE gestations, in healthy spontaneous, homologous and heterologous ART pregnancies. Serum of 4 groups of women, who were followed through two or three trimesters, were collected: PE, patients diagnosed with PE; OD, oocyte donation recipients; HOM, homologous ART women; Sp, spontaneous physiological pregnancy. Our results indicate that PE patients were characterized by lower levels of anti-C1q. In ART pregnant women, the trend of C1q and anti-C1q levels resulted similar to not pregnant women (NP) and to PE patients, even though these women did not develop PE-like symptoms during pregnancy. This finding suggests an immunological dysfunction at the foetal-maternal interface in ART pregnancies, a hypothesis confirmed by the observation of C1q deposition in placentae derived from OD, comparable to PE. Since a significant difference in anti-C1q level was present between PE and healthy control sera, we hypothesize the possible binding on placental syncytiotrophoblast microvesicles (STBM), which are increased in the circulation of PE mothers. Furthermore, the characterization of the binding-epitope of anti-C1q revealed that “physiological” autoantibodies were mainly directed against C1q globular domain. We concluded that anti-C1q could have a physiological role in pregnancy: during the healthy spontaneous pregnancy the physiological increase of these autoantibodies could be important for the clearance of STBM. In PE and in pathological pregnancies (but also in OD pregnancies), the increase of syncytiotrophoblast apoptosis and the consequently the increase of circulating STMB levels, leads to a consumption of C1q and anti-C1q.